Нелинейная динамика системы твердых тел с управляемыми электромагнитными демпферами - Плахтиенко, Н.П.; Забуга, А.Т. (Прикладная механика, 2010)
A nonlinear mathematical model of translational vibrations of a system of n rigid bodies is constructed for the case of inertial loading. The system contains the supportball mechanism of seismic isolation and the electromagnetic dampers, controlled by means of the inertial feed-back channel. When the accelerative damping being presented in the system, the system of differential equations of dynamics is obtained in the normal form. The frequencies of small non-attenuated vibrations are evaluated. A technique of studying the dynamical coefficients by use of acceleration of rigid bodies is proposed for the case of accelerative damping. For the two-mass system, the phenomenon of double phase-frequency resonance is studied.